Circular RNAs Biogenesis and Functions (Advances in Experimental Medicine and Biology,, 2018)
This book provides an essential overview of the rapidly advancing field of circular RNAs - newly discovered RNAs that are generated by back-splicing precursor mRNA and perform regulatory functions in many biological processes. Although many aspects of circular RNAs' biology and mechanisms of gene regulation remain unclear, they have been found to be abundant, evolutionally conserved, and stable in cells; further, they have numerous potential functions. The book consists of eight parts:1) An overview of circular RNAs, 2) Bioinformatics for circular RNAs, 3) Biogenesis of circular RNAs, 4) Molecular mechanisms and gene regulation of circular RNAs, 5) Circular RNAs as potential disease biomarkers, 6) Circular RNAs and human diseases, 7) Circular RNAs in Plants and in Archaea, and 8) Future prospects. Given its focus, the book will be especially useful for researchers and students in the fields of biochemistry, molecular biology, cell biology, and medicine.